System development of silicon photonics links for CERN experiments and accelerators. (1st March 2023) - Scarcella, C.; Detraz, S.; Lalović, M.; Marcon, L.; Olanterä, L.; Prousalidi, T.; Sandven, U.; Sigaud, C.; Soós, C.; Troska, J.
Abstract: Future upgrades of the CERN Experiments and Accelerators require optical links capable of handling the large data volume generated in particle detectors and beam position (BPMs) sensors. Silicon Photonics optical transceivers are a promising candidate to process the required data rate as well as efficiently operate in the harsh radiation environment. We present the experimental characterisation of silicon modulators together with demonstration of optical transmitters based on custom designed Silicon Photonics integrated circuits.